Do Methane Gas Prices Interact with Stock Indices? - Nicoleta BARBUTA-MISU; Teodor HADA; Iulia Cristina IUGA; Dorin WAINBERG (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
This study investigates the short-term relationship between natural gas prices and stock market index prices for six countries (five of G7 member economies and China) spread on three continents, using the VAR model and the Granger causality test. To achieve this goal was examined the correlation between the stock market indices rates of natural gas (NG), European FTSE 100, DAX 30, CAC 40, American DJI and SP 500, Asian Nikkei 225 and SSEC. These eight daily index values were used for the period February 24, 2022, when the geo-political conflict (Russia-Ukraine) began, to May 27, 2022, when large fluctuations in energy prices were observed. This study tries to answer the question of whether there are concrete links and responses to volatility between the natural gas market and stock indices in six advanced economies in the first three months after the start of the Russia-Ukraine geo-political conflict. According to the results achieved using the VAR model and the Granger causality test, the price of natural gas (NG) is the main cause of the evolution of any of the considered stock indices. Overall, the study provides important insights into the complex dynamics of the energy market and its interactions with the broader economy and financial system.